Sodium triphosphate–capped silver nanoparticles on a decellularized scaffold-based polyurethane vascular patch for bacterial infection inhibition and rapid endothelialization. (July 2019) - Li, Yajuan; Liu, Cheng; Mo, Hong; Zhang, Jun; Jiang, Xuefeng; Zhang, Luxia; Yang, Lutao; Fu, Lei; He, Lei; Zhao, Yue; Shen, Jian; Qiao, Tong
With increasing incidence rate of cardiovascular diseases and implant-related infections, there is growing demand for vascular patches that can promote endothelialization and resist bacterial infection. In this work, we immobilized sodium triphosphate–capped silver nanoparticles onto a polyurethane film to obtain a composite film and evaluated its in vitro biocompatibility. Subsequently, we anchored sodium triphosphate–capped silver nanoparticles onto a polyurethane-coated decellularized scaffold to prepare a vascular patch and investigated its in vivo performance in a mouse model. The prepared vascular patch demonstrated excellent biocompatibility and potent antibacterial activity against Escherichia coli and Staphylococcus aureus . It still maintained the surgical artery patency at 30 days after implantation. At the same time, the endothelialization at the surgical site was achieved, showing its ability to facilitate endothelialization. Therefore, it may be a promising candidate for combating bacterial infection and treating diseased blood vessels.